Penjualan Gabin Fla Susu Menggunakan Website - Mujur; Dhera, Alya; Arifin, Arfanita Indriyani; Nurmia; Gemayel, Amin Bintang; Sapar (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Utilizing a website in selling creative food products can arouse the interest of potential buyers in the buying and selling process because the quality and trustworthiness of the products sold is guaranteed, gabin biscuits are the basic ingredient and flan is the filling and the sales instrument via the website adds to the impression of modernizing MSMEs in order to create advanced MSMEs for Indonesia. This Gabin Fla product also adds value to students' creativity because it is almost impossible to find this product in grocery stores or supermarkets in the Palopo area. The methods for implementing this program are input, process (production), output, and evaluation. The results of this program are input, conducting market surveys to determine market conditions. Next is a feasibility study of the business to be run. The final stage is selecting materials and providing a place as well as facilities and infrastructure to support the production process. Process (production), the process of making gabin fla starts from the preparation of materials and tools until the milk gabin fla is ready to be marketed. Output, namely the creative result of milk gabin fla which is ready to be consumed and marketed to consumers. The final one is evaluation, namely this stage is carried out when the production of milk gabin fla products has been completed. At this stage we will review what shortcomings make consumers dissatisfied with consuming our products. Conclusion: selling gabin fla using this website which has sales value can provide skills to students to remain innovative and creative in processing traditional snacks by innovating with websites, providing opportunities for students to practice entrepreneurship with a comprehensive, modern understanding of entrepreneurial concepts, and building student enthusiasm for keep doing business.